In vitro Selective Effect of Imidazole Derivatives as Inhibitors of Human Laryngeal Carcinoma - Vasyl Kovalishyn; Sergiy Rogalsky; Diana Hodyna; Petro Borysko; Larysa Metelytsia (Bioactivities, 2025)
Laryngeal cancer represents a significant portion of head and neck malignancies, greatly affecting quality of life. Despite advancements in treatment, late-stage mortality remains high. The HEp-2 cell line, derived from human laryngeal carcinoma, serves as an in vitro model for studying this cancer. We present in vitro results highlighting the activity of imidazole-based ionic liquids and lysosomotropic detergents as selective inhibitors of laryngeal cancer growth using the HEp-2 cell line, alongside non-oncogenic MRC-5 and HEK-293 cell lines. A comparative analysis of the selectivity coefficients reflecting the action of these imidazole derivatives on HEp-2 cancer cells, compared to their effects on MRC-5 fibroblasts and HEK-293 kidney cells, revealed that the compounds 1-dodecyl-3-methylimidazolium chloride, 1-decyloxycarbonylmethylimidazole, and 1-dodecyloxycarbonylmethyl-3-methylimidazolium chloride appear to be promising candidates with selective activity against laryngeal cancer, with anticancer selectivity coefficients ranging from 2.8 to 11.5 and 2.2 to 20.1, respectively. Especially promising is 1-dodecylimidazole, which has an average selectivity coefficient of 47,675 based on IC₅₀ values for the two non-oncogenic cell lines. Notably, the selectivity coefficients of these compounds were significantly higher—by two or more times—than those of the drug cisplatin.